Case Report: Unclassified Renal Cell Carcinoma With Medullary Phenotype and SMARCB1/INI1 Deficiency, Broadening the Spectrum of Medullary Carcinoma - Valeri, Marina; Cieri, Miriam; Elefante, Grazia Maria; De Carlo, Camilla; Rudini, Noemi; Lughezzani, Giovanni; Buffi, Nicolò Maria; Terracciano, Luigi Maria; Colombo, Piergiuseppe (Frontiers in Medicine, 2022)
Renal medullary carcinoma (RMC) is a rare entity with poor prognosis bearing inactivating genomic alterations in SMARCB1/INI1 resulting in the loss of expression of INI1 and occurring in young patients with sickle cell trait or sickle cell disease. Recently, rare examples with histological characteristics of RMC have been described in older patients without hemoglobinopathies and provisionally termed “Renal cell carcinoma unclassified with medullary phenotype” (RCCU-MP). Fluorescence In Situ Hybridization (FISH) can detect alterations in SMARCB1/INI1 consisting mostly in inactivating translocation of one allele and deletion of the second. To date, only 7 further cases of RCCU-MP have been described in literature. Here we report the second Italian case of RCCU-MP, a 62-year-old man presenting with persistent dull back pain and incidentally discovering a 13 cm mass in the right kidney. The nomenclature of this entity is still debated and might be updated as variant of medullary carcinoma in the upcoming WHO classification. In the meantime, we encourage awareness for these extraordinarily rare neoplasms with poor outcome.